STRATEGI MENINGKATKAN KUALITAS PELAYANAN DAN TARGET KINERJA SUMBER DAYA APARATUR DI SEKRETARIAT DPRD KABUPATEN REMBANG - Hania Rosa Amalia; Siti Sumiati (Jurnal Ilmiah Penelitian Mahasiswa, 2022)
The purpose of making this article is to analyze the Service Quality and Performance Targets ofApparatus Resources at the DPRD Secretariat of Rembang Regency, to describe the vision,mission, goals, strategies and policies of the Secretariat to improve services to DPRD members.In Improving the Performance of State Civil Apparatus at the DPRD Secretariat of RembangRegency, it is necessary to provide quality service performance so that DPRD Members havethe openness to provide clear and precise information as itis so that DPRD Members feel howappropriate and accurate services are and can be accounted for for the interests andsatisfaction of Members. Board.The result of this research is that the performance of the Secretariat of the Regional People'sRepresentative Council in facilitating the implementation of the tasks of the Rembang RegencyRegional People's Representative Council has generally been optimal. Obstacles faced in theform of inadequate ASN staff resources, and the presence of discommunication, inadequatefacilities and infrastructure and budget allocations. The strategy carried out is by increasingthe resources of ASN or staff and implementers by participating in human resource developmentactivities such as technical guidance, seminars or workshops besides providing opportunities toincrease their level of education and providing direction and explanation, asking and invitingstaff to be serious. in carrying out their duties, equipping facilities and infrastructure,proposing additional budget allocations and communicating between the Secretariat and theDPRD.